“Sustainable Beef”. Práticas para a Sustentabilidade na Cadeia da Carne Bovina Gaúcha - Minelle Enéas da Silva (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
It is increasingly apparent the need for discussions on practices for sustainability in different economic sectors and business context. With this perspective, this article aims to analyze how different beef chain members of Rio Grande do Sul are involved with responsible practices, seeking for a more sustainable chain. Therefore, interviews were conducted with stakeholders during the trade show Expointer, during 2012, in order to understand how the interaction between these members and other actors occurs, and to understand how the sustainability is being introduced in beef production. The results indicate that, within its obligations, each member has sought fit, even for the economic mo- tivation, to the new emerging context. Furthermore, we identified that the actions are being incipient developed, however, the actions encompass both environmental and social dimensions, as the animal welfare practice for a more sustainable chain.